Law and Love in Abraham's Binding of Isaac. (3rd July 2015) - Neoh, Joshua
Abstract : Law and love are two distinct modes of association. They offer two different ways of relating to others and the world. They provide two alternative paradigms within which we could view and appreciate our relationships. The methodology of this article is to illustrate this argument through a close reading of a particular narrative: Abraham's binding of Isaac. It begins by setting out the paradigms of law and love before exploring the various ways in which these paradigms converge and diverge. It then presents an interpretation of the narrative of Abraham's binding of Isaac and posits four different permutations of the paradigms of law and love that one could use to engage with the narrative.